A Comissão Pastoral da Terra (CPT) e sua atuação junto aos movimentos sociais rurais nas décadas de 1970 e 1980 no Oeste do Paraná - Castelano, Maria José (2018)
The objective of this study is to analyze the genesis and performance of the Pastoral Land Commission (PLC) and its role with the movements of rural workers. In an ecumenical work between Catholics and Lutherans, the work of the PLC was relevant in the mobilization of demands and resistance during the military dictatorship in the West of Paraná. It seeks to identify the criticisms and the possible solutions directed to the problems that afflicted indigenous, small farmers, squatters and rural workers in the process of economic modernization of the last agricultural frontier in Paraná, and to understand if the PLC exerted an ideological function in the direction of the emerged movements in the 1970s and 1980s